Gastronomic Identities: The Role of Food in Cultural Belonging - ., Priyadarshini S; Bindu, M.R; Sumathy, M.; Dorathy, A Anne (Journal of Ecohumanism, 2024)
Literary works provide cultural values, ideas, and attitudes in order to shed light on the habits and beliefs of numerous cultures. A multitude of heterogeneous cultures coexist worldwide, each encompassing a plethora of viewpoints and convictions. Authors often acquaint readers with diverse cultures in addition to expressing their own perspective. Literary works convey cultural values through the author’s expression. Food has garnered interest from diverse fields, particularly economics, literature, human rights, ethics, sociology, anthropology, and others. Multiple studies have been undertaken to explore the importance of food for the human race. Food is employed in literary works as a means to examine and explore cultural disparities. Anita Desai’s novel, Fasting Feasting, is replete with metaphorical allusions to food and consumption. The novel’s title suggests the concept of consumption, exploring how characters interact with food to reveal disparities in who feasts and starves. This paper focuses on the analysis of narrative that revolve around culinary elements, such as metaphors, symbols, and representations, and their connections to identity and culture.